Didáctica crítica de los aprendizajes de los estudiantes a formar parte de la Policía Nacional - Andino Jaramillo, Alex Fabián (2018)
This study was carried out in the GOE-Guano Police Training School. For its accomplishment, 66 aspirants participated, in which a moderm and transformative teaching was proposed in the pre-profesional subjects of Weapons and Shooting and Police Procedures, determining that the Without Pencil Without Notebook methodology and Socialized Learning contribute in an efficient way to achieve the teaching-learning process in an optimal way, with the objetive of demonstrating how the Critical Didactics satisfies the learning of the aspirants to become a part of the National Police. This allows in yhe field of Security, to increase quality standards in service to society in general. The research in descriptive, correlational, applied with a quantitative focus. The Unit of Analysis corresponds to66 aspirants to become a part of the National Police, to whom the proposed methodology was applied and the data obtained were processed using the SPSS statistical tool. After analyzing the grades obtained by the students in previous years before starting the application of the guide, an academic performance higther tan 9.1 is shown (historical data). As a conclusion, the Critical Didactics by means of the socialized Without Pencil Without Notebook method strengthens the learnings promoting the development of logical thinking in students to become a part of the Nacional Police, academic period December 2017 – May 2018, the application of the guide Critical Didactics in the Learning of Weapons – Shooting and Police Procedures in the students who are aspirants in the GOE-Guano Police Training School, cohort 2019 is recommended since its use improved the development of the clases taught and allowed the teaching-learming process during this academic period.